Vowel systems of the Chibchan languages - Krohn, Haakon Stensrud (2021)
This paper presents the phonological vowel systems of 16 Chibchan languages, according to existing descriptions. The purpose is to provide a basic and systematic overview of the vowel systems found in this family. For each language, the distinctive features needed to distinguish the vowel phonemes are discussed, as well as their phonetic realizations when this is relevant. Whereas the phoneme classification is uncontroversial for many of the languages, there are also some Chibchan languages that have been subject to very different analyses over the years; in these cases, a more thorough discussion is provided. At the end of the paper, the Chibchan vowel systems are compared from a quantitative perspective.